Are Gaming-Enabled Graphic Processing Unit Cards Convenient for Molecular Dynamics Simulation?. (May 2019) - Biagini, Tommaso; Petrizzelli, Francesco; Truglio, Mauro; Cespa, Roberto; Barbieri, Alessandro; Capocefalo, Daniele; Castellana, Stefano; Tevy, Maria Florencia; Carella, Massimo; Mazza, Tommaso
In several fields of research, molecular dynamics simulation techniques are exploited to evaluate the temporal motion of particles constituting water, ions, small molecules, macromolecules, or more complex systems over time. These techniques are considered difficult to setup, computationally demanding and require high specialization and scientific skills. Moreover, they need specialized computing infrastructures to run faster and make the simulation of big systems feasible. Here, we have simulated 3 systems of increasing sizes on scientific- and gaming-enabled graphic processing unit (GPU) cards with Amber, GROMACS, and NAMD and measured their performance accounting also for the market prices of the GPU cards where they were run on.